2007
DOI: 10.1097/scs.0b013e31814b2b8c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment Outcome and Stability Between Distraction Osteogenesis and LeFort I Osteotomy in Cleft Patients With Maxillary Hypoplasia

Abstract: The purpose of this study was to compare treatment outcome and relapse between maxillary advancement surgery with LeFort I osteotomy and maxillary distraction osteogenesis in patients with cleft lip and palate with maxillary hypoplasia. The sample consisted of a maxillary advancement surgery with LeFort I osteotomy group (group 1, N= 14, mean age, 21.7 years) and a maxillary distraction osteogenesis group (group 2, N = 11, mean age, 16.3 years). Lateral cephalograms were taken and traced at presurgery (T0), po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 23 publications
2
47
1
Order By: Relevance
“…This could very well explain why AMD has greater change in pronasale. Even though studies conducted by Baek et al [11] and Chua and Cheung [13] reported that nasolabial angle increased more in distraction group than in conventional orthognathic surgery, no significant variation was observed in the present study. Nasolabial angle was better improved in AMD group when compared to ALO group.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This could very well explain why AMD has greater change in pronasale. Even though studies conducted by Baek et al [11] and Chua and Cheung [13] reported that nasolabial angle increased more in distraction group than in conventional orthognathic surgery, no significant variation was observed in the present study. Nasolabial angle was better improved in AMD group when compared to ALO group.…”
Section: Discussioncontrasting
confidence: 55%
“…Though Cheung et al [6,7,10,11,13] reported no major differences in clinical morbidities between distraction osteogenesis and conventional osteotomy, skeletal and soft tissue stability was better with distraction. The present study goes hand in hand with the results published by Cheung et al For larger movements AMD appears to offer greater stability than that seen with conventional osteotomies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 If the amount of maxillary advancement is large and the patients and parents want a relatively short-term treatment, distraction osteogenesis during adolescence or orthognathic surgery in adulthood can be recommended.…”
Section: Overcorrectionmentioning
confidence: 99%
“…One physical reason for the clockwise rotation of the maxilla during distraction even though these distractors were designed to be rigid is that the distraction force was applied above the maxillary center of resistance and so the rotation was introduced by a simultaneous forward movement. In contrast, some external devices are fixed with the teeth and so are below the center of resistance, causing counter-clockwise rotation of the maxilla and additionally offer the advantage to alter the vector during distraction [4,16]. The extreme scarring in our patients after repair of cleft lip palate and after velopharyngoplasty should not be underestimated.…”
Section: Discussionmentioning
confidence: 94%